White Paper - Open Science in a Digital Republic - Strategic Guide - Scientific and Technical Information Department - CNRS (OpenEdition Press, 2017)
These Study Review and Proposals have been designed to structure and facilitate the implementation of the Act: they therefore concur with the positions adopted by the sponsors of the White Paper Open Science in a Digital Republic, who all clearly wish to associate this new vision for research with practices that will enable it to become a reality. As a supplementary report to the White Paper, these Guidelines aim to assist players in what are often complex procedures: researchers, technician...